2014
DOI: 10.5717/jenb.2014.18.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, but not quercetin, ameliorates inflammation, mitochondrial biogenesis, and lipid metabolism in skeletal muscle after strenuous exercise by high-fat diet mice

Abstract: [Purpose]The purpose of this study was to investigate whether moderate exercise and quercetin intake with a low fat diet contribute to inflammatory cytokine production, mitochondrial biogenesis, and lipid metabolism in skeletal muscle after strenuous exercise by high-fat diet mice.[Methods]Male C57BL/6 mice were randomly divided into four groups: (1) High-fat for 12 weeks and low-fat diet control (C; n = 6); (2) high-fat diet for 12 weeks and low-fat diet with quercetin (Q; n = 4); (3) high-fat diet for 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…Although one previous study reported that 100-250 mg/kg quercetin increased caspase-3 activity in the mouse liver and brain (Choi and Kim 2010), many more studies suggest that quercetin is safe even at very high concentrations (950 mg/kg and 3000 mg/kg) (Barrenetxe et al 2006;Harwood et al 2007;Ruiz et al 2009). Another recent study showed that exercise, but not quercetin, improved mitochondrial biogenesis in soleus muscles, but they used only 10 mg/kg quercetin in their study (Kwon et al 2014). In our study, we observed that quercetin showed only a modest protective effect in MitoPark mice, possibly because of the fact that the MitoPark mouse is the most severe model of PD.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Although one previous study reported that 100-250 mg/kg quercetin increased caspase-3 activity in the mouse liver and brain (Choi and Kim 2010), many more studies suggest that quercetin is safe even at very high concentrations (950 mg/kg and 3000 mg/kg) (Barrenetxe et al 2006;Harwood et al 2007;Ruiz et al 2009). Another recent study showed that exercise, but not quercetin, improved mitochondrial biogenesis in soleus muscles, but they used only 10 mg/kg quercetin in their study (Kwon et al 2014). In our study, we observed that quercetin showed only a modest protective effect in MitoPark mice, possibly because of the fact that the MitoPark mouse is the most severe model of PD.…”
Section: Discussioncontrasting
confidence: 52%
“…Another recent study showed that exercise, but not quercetin, improved mitochondrial biogenesis in soleus muscles, but they used only 10 mg/kg quercetin in their study (Kwon et al . ). In our study, we observed that quercetin showed only a modest protective effect in MitoPark mice, possibly because of the fact that the MitoPark mouse is the most severe model of PD.…”
Section: Discussionmentioning
confidence: 97%
“…We found that IL-6, TNF-α and MCP-1 were significantly reduced and so were MCD, ACC and SREBP-1 [32].…”
Section: Discussionmentioning
confidence: 67%
“…Body weight, weight gain and food efficiency ratio (FER) values did not differ across the SC and EC groups at the end of the experiment, whereas those of the GV group were significantly reduced (Supplementary data 1, supporting information). Kwon et al . reported that continuous exercise can improve insulin sensitivity and decrease body weight and body fat.…”
Section: Resultsmentioning
confidence: 99%